Electrical Characterization of Postmetal Annealed Ultrathin TiN Gate Electrodes in Si MOS Capacitors - Z. N. Khan; S. Ahmed; M. Ali (Advances in Materials Science and Engineering)
Focusing on sub-10 nm Silicon CMOS device fabrication technology, we have incorporated ultrathin TiN metal gate electrode in Hafnium Silicate (HfSiO) based metal-oxide capacitors (MOSCAP) with carefully chosen Atomic Layer Deposition (ALD) process parameters. Gate element of the device has undergone a detailed postmetal annealed sequence ranging from 100°C to 1000°C. The applicability of ultrathin TiN on gate electrodes is established through current density versus voltage (J-V), resistance versus temperature (R-T), and permittivity versus temperature analysis. A higher process window starting from 600°C was intentionally chosen to understand the energy efficient behavior expected from ultrathin gate metallization and its unique physical state with shrinking thickness. The device characteristics in form of effective electronic mobility as a function of inverse charge density were also found better than those conventional gate stacks used for EOT scaling.